2007
DOI: 10.1364/ol.32.001716
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric characterization of ultrashort deep ultraviolet pulses using a multiphoton ionization mass spectrometer

Abstract: The temporal characterization of a femtosecond laser pulse in the deep ultraviolet region using an interferometric autocorrelation scheme is demonstrated. Two-photon ionization of a molecule in a time-of-flight mass spectrometer was used as a nonlinear detector to obtain an autocorrelation trace. This setup proved useful in not only providing a temporal characterization of a pulse but also investigating the ultrafast dynamics of photochemical processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In the following FRAC measurement, NO [16] and Xe were simulta- Fig. 4(a) is consistent with the theoretically predicted shape of the FTL pulse shown in Fig.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…In the following FRAC measurement, NO [16] and Xe were simulta- Fig. 4(a) is consistent with the theoretically predicted shape of the FTL pulse shown in Fig.…”
Section: Methodssupporting
confidence: 85%
“…This implies that Xe isotopes can provide a third-order nonlinear response over a wide spectral range (204 -306 nm) and would be useful for measuring the temporal profiles of ultrashort optical pulses by avoiding these two resonance wavelengths in the DUV region. The secondorder nonlinear response measured using NO as a nonlinear medium for multiphoton ionization has already been reported elsewhere [16]. An ionization energy that is lower for NO (9.26 eV) than for Xe, and the high energy level of the first excited singlet state (4.13 eV), limits the bandwidth for a second-order nonlinear response.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…For simple on-site measurement of pulse widths, a device based on fringe-resolved autocorrelation (FRAC) was developed, which consisted of an interferometer and a time-of-flight mass spectrometer that was used as a two-photon-response detector to measure a non-resonant two-photon ionization signal [18][19][20][21]. However, the laser beam must be split into two parts and recombined after the interferometer, which reduces the laser pulse energy and then the sensitivity of the mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…A GaN diode with a nature of two-photon absorption in the VIS region (at round 400 nm) has been employed as a detector in a fringe-resolved autocorrelator (FRAC) [7]. In a previous study, we reported on the development of an FRAC, in which a mass spectrometer was employed as a two-photon-response device in the DUV region (at around 267 nm) [8]. However, the frequency domain of these techniques is limited to one octave [9].…”
Section: Introductionmentioning
confidence: 99%